Genome Sequence of Mycoplasma feriruminatoris sp. nov., a Fast-Growing Mycoplasma Species - Fischer, Anne; Santana-Cruz, Ivette; Giglio, Michelle; Nadendla, Suvarna; Drabek, Elliott; Vilei, Edy M.; Frey, Joachim; Jores, Joerg (American Society for Microbiology, 2013)
Members of the “Mycoplasma mycoides cluster” represent important livestock pathogens worldwide. We report the genome sequence of Mycoplasma feriruminatoris sp. nov., the closest relative to the “Mycoplasma mycoides cluster” and the fastest-growing Mycoplasma species described to date.